Thermal conductivity of solid paraffins and several n-docosane compounds with graphite - Paul, Andreas; Baumhögger, Elmar; Dewerth, Mats-Ole; Hami Dindar, Iman; Sonnenrein, Gerrit; Vrabec, Jadran (Journal of Thermal Analysis and Calorimetry)
The technical importance of paraffins as phase change materials (PCM) in heat storage systems increases. Knowledge on the thermal conductivity of paraffins is necessary for the design and optimization of heat storage systems. However, for most paraffins solely the thermal conductivity of the liquid state has been sufficiently investigated. For the solid state, precise thermal conductivity data are only known for a few paraffins, while only generalized values are available for the remainder, some of which contradict each other. In this study, a measurement setup based on the modified guarded hot plate method is developed. It is used to investigate the thermal conductivity of several paraffines in the solid state, including pure n-docosane and its compounds with different types and concentrations of graphite. For n-docosane in the solid state, the thermal conductivity is determined to be 0.49 W/(m K). A particle size of 200 μm with a spherical shape turns out to be optimal to increase the thermal conductivity. This allows the thermal conductivity of a compound with 10% graphite to increase by a factor of three compared to the pure paraffin. Furthermore, significant differences to thermal conductivity data from the literature are found.
Keywords: Physical and Theoretical Chemistry; Condensed Matter Physics

Determining the heat flow through the cabinet walls of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Moczarski, Lukas; Reineke, Michael; Sonnenrein, Gerrit; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Freiberger, Alfred; et al. (International Journal of Refrigeration)
The increase of the thermal conductivity of PUR foam in the insulation of the cabinet is an important cause for aging processes of household refrigerating appliances. To determine the influence of the PUR foam aging on energy consumption, the development of a new measurement method is necessary be- cause current methods influence the aging behavior of household refrigerators and are therefore not applicable in general. Based on a latent heat sink, constructed as an ice water bucket, a new measure- ment method is developed to determine the k ·A value over time. With this method, the k ·A value of four household refrigerating appliances was determined over an interval of 14 months. The k ·A value increased between 3.6% and 11.5% during this period.

Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Morbach, A.; Neukötter, Moritz; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
The influence of latent heat storage elements on the cooling performance and the temperature rise time of household refrigerating appliances is studied experimentally in the context of the “new global refriger- ator standard”IEC 62552:2015. In addition to the daily energy consumption, this international standard- ization introduced performance tests for cooling capacity and temperature rise time. While the cooling capacity has long been anchored in various test procedures of consumer organizations, the temperature rise time, which has only been tested on freezers so far, will be a decisive factor in the future. Moreover, the need for so-called "smart appliances" that may balance power consumption is increasing since such devices may compensate the volatility of renewable energies and thus stabilize the power grid. Against this background, eight commercial household refrigerators and refrigerator-freezers are equipped with polymer-bound phase change materials (PCM) and their performance is determined under the new stan- dard test conditions. The results show that the introduction of PCM increases the cooling capacity by up to 33 % and also increases the temperature rise time by up to 145 %, without affecting power consump- tion, as compared to the unmodified refrigeration appliances.

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (CHEMICAL ENGINEERING TRANSACTIONS)

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Bestimmung von Wärmeverlusten in Haushaltskältegeräten - Paul, Andreas; Moczarski, Lukas; Gieselmann, Mirko; Reineke, Michael; Elsner, Andreas; Baumhögger, Elmar; Sonnenrein, Gerrit; Vrabec, Jadran
Wie jedes technische System unterliegen auch Haushaltskältegeräte einer alterungsbedingten Degeneration, die zu einem Anstieg der Energieaufnahme über die Lebensdauer dieser Geräte führt. Ursache hierfür sind verschiedene Effekte, die in dem vom BMWi geförderten Projekt ALGE untersucht werden. Aus den so gewonnenen Erkenntnissen sollen dann degenerationsbeständigere Haushaltskältegeräte entwickelt werden. Eine wichtige Alterungsursache ist der Anstieg der Wärmeleitfähigkeit des PUR-Schaums der Gehäuseisolierung. Zur Bestimmung dieses Einflusses auf die Energieaufnahme ist die Entwicklung neuer Messmethoden notwendig, die zerstörungsfrei sein und den realen Anwendungsbedingungen möglichst nahekommen sollen. Dazu wurde eine Wärmesenke entwickelt, die den Geräteinnenraum unabhängig vom Kältekreislauf abkühlt. Die Wärmesenke ist als Eiswasserbehälter ausgeführt, sodass die Schmelzenthalpie des Eises die durch die Isolierung in den Geräteinnenraum einfallende Wärme aufnimmt. Durch die Bestimmung der Abtauzeit einer bestimmten Eismenge kann so der alterungsbeeinflusste 𝑘∙𝐴-Wert des Gehäuses von Haushaltskältegeräten bestimmt werden.

Wassergekühltes On-Board-Ladegerät mit optimiertem Kühlkanal - Bolte, Sven; Henkenius, Carsten; Böcker, Joachim; Kenig, Eugeny; Zibart, Alexander; Figge, Heiko (wt Werkstattstechnik online)
Für On-Board-Ladegeräte sind brückenlose netzfreundliche Gleichrichter in Kombination mit einem Resonanzkonverter empfehlenswert. Auf diese Weise lassen sich Verluste minimieren und es wird eine hohe Leistungsdichte erreicht. Darüber hinaus wurde der Kühlungskreislauf des Ladegeräts durch CFD (Computational Fluid Dynamics, rechnergestützte Flüssigkeitsdynamik)-Simulationen des Kühlkanals optimiert, um einen bestmöglichen Wärmeübergang bei geringem Druckabfall zu erzielen.

Water-cooled on-board charger with optimized cooling channel - Bolte, Sven; Henkenius, Carsten; Böcker, Joachim; Zibart, Alexander; Kenig, Eugeny; Figge, Heiko (2017 19th European Conference on Power Electronics and Applications (EPE'17 ECCE Europe))

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Fieback, K.; Morbach, A.; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
This study presents the results of an experimental investigation of the influence of latent thermal heat storage elements on the power consumption as well as the temperature distribution of commercial household refrigerators.Two evaporator types and a standard wireand- tube condenser are equipped with copolymer-bound phase change materials (PCM) and the performance is determined under standard conditions. The results show that refrigerating appliances equipped with PCM can be optimized through modifications of the control strategy to achieve different targets: (a) Power consumption can be significantly reduced by increasing the evaporator and decreasing the condenser temperature. (b) Temperature fluctuations in the refrigerator’s fresh-food compartment during the cooling cycle can be reduced from 4 °C to 0.5 °C. (c) The cooling cycle duration can be tripled without compromising the fresh-food compartment conditions. The latter may help to meet the growing demand for balancing power consumption to stabilize the power grid, e.g. if the share of highly fluctuating, sustainable energy supply is large.